Using a co-design process to develop an integrated model of care for delivering self-management intervention to multi-morbid COPD people in rural Nepal - Yadav, Uday Narayan (Health Res Policy Syst, 2021)
BACKGROUND: People with chronic obstructive pulmonary disease (COPD) in Nepal are not receiving adequate support to self-manage their chronic conditions, and primary health care can play a key role in the effective management of these. In this study, we aimed to develop a model of care, using a co-design approach, for delivering evidence-based biomedical and psycho-social care to support self-management for people with multi-morbid COPD in rural Nepal. METHODS: A co-design approach, guided by the five stages of the design thinking model, was used for this study. Layering on “empathize” and “define” phases, we ideated a model of care that was further refined in a “prototype” stage, which included a series of consultative meetings and a 1-day co-design workshop with stakeholders. This co-design process involved a wide range of stakeholders from Nepal, including people with COPD and their families, community representatives, local government representatives, primary care practitioners, community health workers, policymakers, state-level government representatives and academics. RESULTS: Through our co-design approach, a model of integrated care for delivering evidence-based biomedical and psycho-social care to support self-management for people with multi-morbid COPD was designed. The integrated model of care included: screening of the community members aged > 40 years or exhibiting symptoms for COPD and management of symptomatic patients within primary health care, establishing referral pathways for severe cases to and from secondary/tertiary-level health care and establishing a community-based support system. It involved specific roles for community health workers, patients and their caregivers and community representatives. It was built on existing services and programmes linking primary health care centres and tertiary-level health facilities. CONCLUSION: The co-design approach is different from the currently dominant approach of rolling out models of care, which were designed elsewhere with minimal community engagement. In our study, the co-design approach was found to be effective in engaging various stakeholders and in developing a model of care for rural Nepal. This grassroots approach is more likely to be acceptable, effective and sustainable in rural Nepal. Further research is required to test the effectiveness of an integrated model of care in delivering self-management support for people with multi-morbid COPD in rural Nepal.